1992
DOI: 10.1016/0741-5214(92)90721-j
|View full text |Cite
|
Sign up to set email alerts
|

The role of duplex scanning versus angiography in predicting outcome after balloon angioplasty in the femoropopliteal artery

Abstract: Duplex-derived velocity measurements were used to assess the hemodynamics of 64 femoropopliteal arterial sites in 59 patients after angiographically successful percutaneous transluminal balloon angioplasty. With use of angiography as the gold standard, percutaneous transluminal balloon angioplasty was judged to be successful if (1) evidence existed of a "split" caused by intimal dissection and splitting of atherosclerotic plaque; and (2) no significant diameter-reducing residual stenosis was observed at the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…The authors suggested that duplex Doppler assessment of residual stenosis might be superior to angiography, haemodynamic measurement or clinical assessment for predicting the success of PTA. Patients with an increase of peak systolic velocity at the angioplasty site greater than 100 % had a 15 % 1-year patency rate compared with 84 % patency rate of arterial segments with a peak systolic velocity increase less than 100 % [55]. Spijkerboer et al also reported that a residual duplex stenosis 1 day after PTA was prognostic for failure within 1 year [56].…”
Section: Selection For Endoluminal Interventionsmentioning
confidence: 94%
See 2 more Smart Citations
“…The authors suggested that duplex Doppler assessment of residual stenosis might be superior to angiography, haemodynamic measurement or clinical assessment for predicting the success of PTA. Patients with an increase of peak systolic velocity at the angioplasty site greater than 100 % had a 15 % 1-year patency rate compared with 84 % patency rate of arterial segments with a peak systolic velocity increase less than 100 % [55]. Spijkerboer et al also reported that a residual duplex stenosis 1 day after PTA was prognostic for failure within 1 year [56].…”
Section: Selection For Endoluminal Interventionsmentioning
confidence: 94%
“…Some authors recommend Doppler ultrasonic monitoring during the procedure or early duplex surveillance to detect failures after PTA, especially in femoro-popliteal arteries. Using duplex scanning, Mewissen et al [55] showed that a PTA site with velocity spectra of a greater than 50 % residual stenosis can be masked on completion angiography and was predictive of failure as well as clinical deterioration. The authors suggested that duplex Doppler assessment of residual stenosis might be superior to angiography, haemodynamic measurement or clinical assessment for predicting the success of PTA.…”
Section: Selection For Endoluminal Interventionsmentioning
confidence: 98%
See 1 more Smart Citation
“…46 Others identified ultrasound as a valuable tool in identifying residual percutaneous transluminal angioplasty stenosis and found it to be predictive of future restenosis and occlusion. 47 Ultrasound surveillance after stent implantation, on the other hand, allows identification of moderate-to high-grade restenosis at a stage when reintervention may maintain patency of the stent and prevent its occlusion. Once a stent occludes, the durability of any reintervention is limited.…”
Section: Duplex Arterial Ultrasoundmentioning
confidence: 99%
“…Some investigators have suggested that DUS after EVT has no role, 13,14 whereas others have reported that residual stenosis on the initial DUS is a major risk factor for subsequent EVT failure. 15,16 We routinely enroll patients into a DUS protocol after both open bypass and EVT. Our reintervention criteria for DU-detected lesions after infrainguinal bypass follow established parameters.…”
mentioning
confidence: 99%